PARTISIPASI PETANI DALAM PROYEK PENGEMBANGAN KAWASAN INDUSTRI MASYARAKAT PERKEBUNAN (KIMBUN) JAMBU METE DI KECAMATAN JATISRONO KABUPATEN WONOGIRI - Dwi Sularsih; Djiwandi Djiwandi; Emi Widiyanti (Universitas Sebelas Maret, 2006)
The KIMBUN project is a concept of agriculture sub sector establishment that was carried out through area and target group approximation. This research was aimed to study the intern and ekstern factor ofthe farmer, to study the level offarmer participation, ang to study the relationship between the intern and ekstern factor ofthe farmer with the level offarmer participation in KIMBUNproject at 2003/2004. Basic method used in this research is descriptive using survey technique. In determining the research location, the researcher use purposive system one subdistrict in Wonogiri regency was in Jatisrono area. They are Megah Buana farmer's group, Sido Mukti, Giri Jaya Mete, Sida Maju, Baik, dan Ngudi Lestari. To find the correlation between the intern factor and ekstern factor ofthe farmer with the level offarmer participation in Kl.MBUN project, the researcher use 's Spearman Rank correlation withSPSS 11. 0for Windows. The research results showed that the level offarmers participation in planning stage are medium category, the level offarmers participation in action stage are high category, the level offarmers participation in benefit results stage are high category, and the level offarmers participation in all of stage are medium category. Age had the real relationship and positive with the farmers participation, formal education had the real relationship and positive with the farmers participation, non formal education had the real relationship with the farmers participation, income did not had the real relationship with the farmers participation, work experience had the real relationship and positive with the farmers participation, cosmopolity did not had the real relationship with the farmers participation, membership didnot had the real relationship with the farmers participation, and the fuction of instructor had the real relationship and positive with the farmers participation.